Molecular docking, drug-likeness and DFT study of some modified tetrahydrocurcumins as potential anticancer agents - Ahmed Mahal; Marwan Al-Janabi; Volkan Eyüpoğlu; Anas Alkhouri; Samir Chtita; Mustafa M. Kadhim; Ahmad J. Obaidullah; Jawaher M. Alotaibi; Xiaoyi Wei; Mohammad Rizki Fadhil Pratama (Elsevier, 2024)
The present study utilized molecular docking and density functional theory (DFT) approaches, and ADMET (absorption, distribution, metabolism, excretion, and toxicity) properties to investigate the binding interactions, reactivity, stability, and drug-likeness of curcumin (1), tetrahydrocurcumin (2), and tetrahydrocurcumin derivatives (3-6) as potential anti-cancer agents. MGL (Molecular Graphic Laboratory) and Discovery Studio Visualizer (DSV) software employed for docking studies. Pharmacokinetic and pharmacodynamic (ADME-Tox) analyses were conducted using SwissADME and pKCSM web servers. Total Electron Density (TED) measurements identified molecular adsorption sites, considering various factors, including quantum chemical characteristics, to assess compound effectiveness using DFT method implanted in the Gaussian software. The binding energy (Eb) from docking simulations was used to evaluate inhibitory potential. ADMET analysis suggested favorable oral bioavailability and pharmacokinetics for all studied substances, excluding compound 4. DFT and docking investigations highlighted compounds 1, 2, and 6 as optimal scaffolds for drug design based on in silico screening tests.